Network Pharmacology Analysis of ZiShenWan for Diabetic Nephropathy and Experimental Verification of Its Anti-Inflammatory Mechanism - Guo X; Wu Y; Zhang C; Wu L; Qin L; Liu T (Dove Medical Press, 2021)
Xiaoyuan Guo,1 You Wu,2 Chengfei Zhang,2 Lili Wu,3 Lingling Qin,4 Tonghua Liu3 1Department of Nephrology, Dong Fang Hospital, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of China; 2Second Clinical Medical College, Beijing University of Chinese Medicine, Beijing, 100078, People’s Republic of China; 3Key Laboratory of Health Cultivation of the Ministry of Education, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of China; 4Technology Department, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of ChinaCorrespondence: Tonghua LiuKey Laboratory of Health Cultivation of the Ministry of Education, Beijing University of Chinese Medicine, 11 Bei San Huan Dong Lu, Chaoyang, Beijing, 100029, People’s Republic of ChinaTel +8601064286426Fax +8601064213817Email thliu@vip.163.comBackground: Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD). The inflammatory response plays a critical role in DN. ZiShenWan (ZSW) is a classical Chinese medicinal formula with remarkable clinical therapeutic effects on DN, but its pharmacological action mechanisms remain unclear.Aim: In this study, a network pharmacology approach was applied to investigate the pharmacological mechanisms of ZSW in DN therapy. Based on the results of network analysis, the core targets and signaling pathways related to anti-inflammatory effect were verified via experiments in vivo.Methods: The candidate chemical ingredients of ZSW as well as its putative targets and known therapeutic targets of DN were acquired from appropriate databases. The “herb-ingredient-target” network for ZSW in DN treatment was established. The protein–protein interaction (PPI) network of potential targets was constructed to screen the core targets. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed. In addition to biochemical and pathological indicators, the core targets and signaling pathways associated with inflammation were partially validated in db/db mice at molecular level.Results: A total of 56 active ingredients in ZSW and 166 DN-related targets were selected from databases. A high proportion of core targets and top signaling pathways participate in inflammation. ZSW markedly alleviated renal injuries pathologically and regulated related biomarkers. In particular, ZSW significantly inhibited the exaggerated release of inflammatory cytokines such as interleukin (IL)-1β, IL-6, tumor necrosis factor receptor (TNF)-ɑ, and monocyte chemotactic protein (MCP)-1 as well as regulating p38 mitogen-activated protein kinases (MAPK) and phosphoinositide 3-kinase (PI3K)–protein kinase B (Akt) signaling pathways in db/db mice.Conclusion: This study first comprehensively investigated the active ingredients, potential targets, and molecular mechanism of ZSW as a therapy for DN. ZSW achieved renoprotective effects in DN via regulation of multiple targets and signaling pathways, especially by alleviating inflammation. Results indicate that ZSW is a promising multi-target therapeutic approach for DN treatment.Keywords: ZiShenWan, network pharmacology, diabetic nephropathy, inflammation